ANALISIS PENGGUNAAN ADJEKTIVA NOMINATIF DALAM BAHASA JEPANG (Berdasarkan Data Sintaksis Corpus) - Puspitosari, Dwi (Universitas Negeri Semarang, 2019)
This study aims to identify nominative adjectives in Japanese that are difficult to categorize based on the occurred changes when these words are produced along with the other words. For non-native Japanese learners, this has become a challenging issue. The main reason is the adjective that was classified into two categories in accordance with their changes, i.e., i-adjectives and na-adjectives. These adjectives presented different forms of change that had a tendency of transforming into nouns when collaborating with other nouns. Not only did learners in elementary and secondary level face the difficulties, but also those in upper levels did. The data in this study focused on adjectives with a high frequency of use that were collected from